2018
DOI: 10.1177/0030222818765807
|View full text |Cite|
|
Sign up to set email alerts
|

The Usage of Digital Resources by Swedish Suicide Bereaved in Their Grief Work: A Survey Study

Abstract: This study examined Swedish suicide bereaved individuals' use of different resources in their grief work and how they value these resources. The material consisted of a web-based survey, which was analyzed with quantitative methods. The results showed that the psychosocial ill-health was severe among the suicide bereaved participants and that a majority used digital resources in their grief work. The propensity to engage in online support groups or memorial websites was not predicted by the severity of psychos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 40 publications
(76 reference statements)
5
21
0
Order By: Relevance
“…Ethical approval for the study was granted by the Regional Ethical Review Board in Stockholm 2016-02-11. A more detailed account of the design and methods has been described elsewhere (Westerlund, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethical approval for the study was granted by the Regional Ethical Review Board in Stockholm 2016-02-11. A more detailed account of the design and methods has been described elsewhere (Westerlund, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Especially strong feelings of guilt, shame, stigmatization, social rejection, and isolation have been put forward as such characteristics (e.g., Bailley et al, 1999;Jordan, 2001;Harwood et al, 2002;Ratnarajah and Maple, 2011;Bell et al, 2012). Shame and stigma have historically, culturally, and religiously surrounded the suicide subject per se but also many of the underlying causes of suicide, such as psychiatric illnesses, drug abuse, and social problems (Westerlund, 2018). Guilt and blameworthiness may be due to that suicide-bereaved people in part see themselves as responsible for their close one's death (Jordan, 2001) and may feel that they should have recognized the signs and prevented the suicide (Lester, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…That grief could indeed be seen as an appropriate response to perceptual world-loss can be motivated via a characterization of grief offered by Michael Westerlund, who in turn invokes psychiatrist and phenomenologist Karl Jaspers’s notion of a limit situation . Westerlund suggests that grief “should not primarily be regarded as a pathological condition…, but rather as a psychosocial and existential limit situation triggered by an overwhelming and disruptive loss in life” ( 2020 ). I wager that “a disruptive loss in life” placing us in “a psychosocial and existential limit situation” is an accurate characterization of the ubiquitous breakdown in perceptual affordances caused by the pandemic.…”
Section: Digital Mental Health and The Loss Of Perceptual World-familmentioning
confidence: 99%
“…In terms of grief reactions, most users of online resources report the importance of finding information about mourning and discussing grief-related topics, which could be taboo or stigmatized topics offline. Despite a shortage of evidence of the effectiveness of online resources, most studies report perceived benefits (23)(24)(25)(26)(27)(28), such as the possibility of using the resources around the clock and discussing griefrelated topics without being judged. Kramer et al (26) reported a significant increase in well-being and a significant decrease in depressive symptoms after 12 months of use of an online forum.…”
Section: Introductionmentioning
confidence: 99%
“…Kramer et al (26) reported a significant increase in well-being and a significant decrease in depressive symptoms after 12 months of use of an online forum. Westerlund et al (28) found that online support group activity was significantly associated with satisfaction regarding psychosocial health (p < 0.001), while memorial website activity showed a tendency to have a negative association (p = 0.05). Having online access to support from other people bereaved by suicide is also highly valued, which is in line with what is known about the experienced value of peer suicide bereavement support (15).…”
Section: Introductionmentioning
confidence: 99%